2020
DOI: 10.1136/annrheumdis-2020-eular.6615
|View full text |Cite
|
Sign up to set email alerts
|

Ab0363 safety of Jak Inhibitors in Patients With Arthritis Rheumatoid Under Real-Life Conditions

Abstract: Background:Efficacy and safety profile of new JAK inhibitors have been properly defined by several clinical trials, being tested in many patients with Arthritis Reumatoid. However, real-life conditions studies play an important role in order to know JAK inhibitors behaviour in safety.Objectives:To describe adverse events of JAK inhibitors in patients with Arthritis Rheumatoid and asses the survival in relation to adverse events.Methods:Observational, descriptive, retrospective design performed in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In the Spanish population, the study with the most extended follow-up of survival was from Soleto et al (45) which showed promising results with tofacitinib at 12 months. The frequency of interruption of treatment due to ineffectiveness is noteworthy, which could be related to refractory patients' clinical profile in the studies and/ or the small sample used (47). The most commonly reported AE in retrospective studies among the Spanish population was HZ infection (45,58), which is in line with results by Kremer et al (31) in the US, where the 5-year incidence rate of AEs was evaluated.…”
Section: Integration Of the Real-world Evidencesupporting
confidence: 72%
See 4 more Smart Citations
“…In the Spanish population, the study with the most extended follow-up of survival was from Soleto et al (45) which showed promising results with tofacitinib at 12 months. The frequency of interruption of treatment due to ineffectiveness is noteworthy, which could be related to refractory patients' clinical profile in the studies and/ or the small sample used (47). The most commonly reported AE in retrospective studies among the Spanish population was HZ infection (45,58), which is in line with results by Kremer et al (31) in the US, where the 5-year incidence rate of AEs was evaluated.…”
Section: Integration Of the Real-world Evidencesupporting
confidence: 72%
“…Between 2019 and 2021, 16 retrospective studies reported the tofacitinib experience in patients with RA on routine clinical practice in Spain (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). Data from case-series were obtained from medical records and databases of a hospital's Rheumatology Service (Supplementary Table S1, http://www.ddtjournal.com/ action/getSupplementalData.php?ID=94).…”
Section: Available Real-world Studies With Tofacitinib For Rheumatoid...mentioning
confidence: 99%
See 3 more Smart Citations